PENGARUH KEMAMPUAN MEMBACA AKSARA AWAL MELALUI KARTU HURUF PADA ANAK USIA 5-6 TAHUNAN (PENELITIAN EKSPERIMEN DI TK MERANTI SETU) - Nunuk Khusnul Huda (Kiddie: Early Childhood Education and Care Journal, 2023)
The background of this research case involves the challenge of enhancing reading skills in 5-6 year old children. Early script comprehension is a crucial foundation in the process of learning to read. This study aims to investigate the impact of using alphabet cards on improving early reading skills in children aged 5-6 years. The experimental research method used in this study is a control group & treatment group pattern. The research sample consisted of children aged 5-6 years at Meranti Setu Kindergarten in 2023. In this study, the control group was given standard learning without using alphabet cards, while the experimental group was given learning using alphabet cards. Measurement of early literacy skills was done before & after the hegemony using a specific test created for this study. The results showed that the group of children who received instruction using alphabet cards experienced a significant improvement in early reading skills compared to the control group. The use of alphabet cards effectively helped children aged 5-6 years share their early reading skills. This study provides evidence that the use of alphabet cards can be an effective method of enhancing early reading skills in 5-6 year old children. The implications of this study can be used by educators & curriculum developers to share learning tactics. The implications of this study can be used by educators and curriculum developers to share more effective learning tactics for teaching reading in early childhood